Islam and Sufism: A Case Study of Qadriya Sufi Order in Construction of Islamic Society - Akher, Dr. Naseem; Rafiq, Dr Shumaila; Akhtar, Dr.Sohail (Acta-Islamica, 2023)
This is an analytical form of study which explores the term Sufism and Qadriyah Sufi order. In this study it has tried to understand the term Sufism and its importance. Basically Sufisim is a alternative word of mysticism which is universally used in the different religion of the world except Islam. There are different concepts and philosophys which interpret the word Sufism and mysticism. In Islam it is thought and considered in the meaning of the individual inner purity and piety. Sufism created simpacity and boosted up the society toward nobility and spirituality of mind and soul. After the initial phase of the historical evolution and development Islamic Sufism served the humanity through several Sufi orders on the basis of same faith under the the teaching of Islamic Shariah. Among these Sufi order Qadriya is one of them and it is considered as a universal Sufi order in the entire Islamic World. Primarily this research is abrief interpretation of the Sufiism along with the Qadriyah Sufi Order. It highlights the significance and role of Qadriya order in the construction of the society.